The Multidimensional Illness Severity Questionnaire: Preliminary evaluation of a brief parent‐reported measure of illness severity. (5th February 2019) - Paquette, Erin T; Joffe, Steven
Abstract : Aim: This study describes the reliability and concurrent validity of the Multidimensional Illness Severity Questionnaire (MISQ), a five‐item measure for capturing parents' reports of their child's illness severity. Methods: We conducted a cross‐sectional survey of parents of children participating in a paediatric research study ( n = 20). We assessed parents' perceptions of illness severity using five measures: (i) the MISQ, (ii) the Lansky Play Performance scale, (iii) the Severity of Illness Scale, (iv) subscales of the Parent Experience of Child Illness and (v) general health. We calculated the internal reliability of the MISQ using Cronbach's alpha and assessed concurrent validity through correlations between scores on the MISQ and other measures. Results: MISQ scores ranged from 6/21 to 17/21 (mean = 11.5). The MISQ had adequate internal consistency (Cronbach's α = 0.76) and correlated strongly with other measures. Conclusion: Preliminary evaluation suggests that the MISQ is an easy‐to‐administer and internally consistent multidimensional assessment of parent‐reported illness severity.